2010
DOI: 10.1101/gad.563210
|View full text |Cite
|
Sign up to set email alerts
|

Histone demethylase KDM5A is an integral part of the core Notch–RBP-J repressor complex

Abstract: Timely acquisition of cell fates and the elaborate control of growth in numerous organs depend on Notch signaling. Upon ligand binding, the core transcription factor RBP-J activates transcription of Notch target genes. In the absence of signaling, RBP-J switches off target gene expression, assuring the tight spatiotemporal control of the response by a mechanism incompletely understood. Here we show that the histone demethylase KDM5A is an integral, conserved component of Notch/RBP-J gene silencing. Methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(172 citation statements)
references
References 51 publications
(63 reference statements)
7
164
0
Order By: Relevance
“…24 Recently, RBP2 protein was shown to be an integral part of the core Notch-RBP-J repressor complex, contributing to switch off the Notch signaling. 25 In contrast to its tumor suppressor function, Sharma et al have shown the link between RBP2 and drug resistance. 26 RBP2 was elevated in drug-tolerant subpopulation of cancer cells, which were treated with a receptor tyrosine kinase inhibitor and RBP2 knockdown significantly reduced the number of drug tolerant population.…”
Section: Rbp2/jarid1a/kdm5amentioning
confidence: 99%
“…24 Recently, RBP2 protein was shown to be an integral part of the core Notch-RBP-J repressor complex, contributing to switch off the Notch signaling. 25 In contrast to its tumor suppressor function, Sharma et al have shown the link between RBP2 and drug resistance. 26 RBP2 was elevated in drug-tolerant subpopulation of cancer cells, which were treated with a receptor tyrosine kinase inhibitor and RBP2 knockdown significantly reduced the number of drug tolerant population.…”
Section: Rbp2/jarid1a/kdm5amentioning
confidence: 99%
“…However, evidence that invertebrate SHARP and CIR1 proteins mediate substantial aspects of Notch target repression in vivo is limited. Recently, the histone demethylases KDM5A/Lid were reported as conserved members of CBF1-Su(H) co-repressor complexes that bind directly to these transcription factors (Moshkin et al, 2009;Liefke et al, 2010), although these chromatin factors have pleiotropic functions involving diverse DNA-binding partners such as Rb, Myc (also known as Dm in Drosophila) and PRC2 (Polycomb repressive complex 2) (Fattaey et al, 1993;Secombe et al, 2007;Pasini et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Domains selected for analysis include fragments responsible for DNA interactions; specifically, the β-hairpin which, in the case of PHD domains, is characterized by the stabilizing presence of zinc (Zn 2+ ) ions. Our selection is motivated by the fact that these domains participate in epigenetic phenomena (histone demethylase activity) [18] as well as in polycomb complexation [19][20][21], both of which are important in the context of pathological (disease-related) processes [22,23].…”
Section: Introductionmentioning
confidence: 99%